PROBLEMS OF DEVELOPING TEACHERS’ DIGITAL COMPETENCE IN THE USE OF GLOBAL EDUCATIONAL TECHNOLOGIES IN PRIMARY EDUCATION (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the challenges of developing teachers’ digital competence in the effective use of global educational technologies in primary education. In the modern educational process, a teacher’s digital literacy is considered a key factor. The article scientifically examines existing problems, their underlying causes, and possible solutions to address them.
Keywords: Digital competence, primary education, innovative technologies, pedagogical skills, digital literacy, quality of education.